2018
DOI: 10.5530/fra.2018.2.19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of Antioxidant Activity of Leaves, Pericarps and Pulps of Three Garcinia Species in Malaysia Yik-Ling Chew, and Yau-Yan Lim

Abstract: Background:Garcinia genus plants are a group of well-known fruit trees in Malaysia.The botanical parts of the trees are used for medicinal purposes, where they are prepared as decoction, pastes for wound infections, and some have been consumed as food. Objectives: This paper focused on the assessment of antioxidant potential of three selected Garcinia species commonly used in Malaysia. Materials and Methods: Fresh plant materials were extracted using maceration, and various antioxidant activities of the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…The cessation of a radical chain reaction can be achieved through the electron donation by a sample possessing significant reducing power, leading to the formation of a stable molecule by the accepting free radical [33,34]. The current investigation found that the EGA's reducing ability was comparable to that of previous studies, as displayed in Figure 1B [35]. Previous research has shown that hydroxyl radicals, which are produced naturally, are highly reactive free radicals, and that humans lack enzymes that can neutralize them [36].…”
Section: Antihyperlipidemic Activitysupporting
confidence: 82%
“…The cessation of a radical chain reaction can be achieved through the electron donation by a sample possessing significant reducing power, leading to the formation of a stable molecule by the accepting free radical [33,34]. The current investigation found that the EGA's reducing ability was comparable to that of previous studies, as displayed in Figure 1B [35]. Previous research has shown that hydroxyl radicals, which are produced naturally, are highly reactive free radicals, and that humans lack enzymes that can neutralize them [36].…”
Section: Antihyperlipidemic Activitysupporting
confidence: 82%
“…Although both species are closely related and collected in a common climatic niche, their general phenolic compound contents and free radical-scavenging capacities were different. This coincides with the different accumulation patterns of phytochemicals observed between closely related species and even in plants of the same variety, indicating that accumulation patterns are influenced by environmental and endogenous parameters [37,38,39]. In the case of the Rhus genus, it has been reported that phenolic compounds and antioxidants vary between species and between populations of the same species.…”
Section: Discussionsupporting
confidence: 71%
“…Garcinia mangostana (Mangosteen) peel is discarded as waste in the agricultural industry. The peel is rich in phytochemicals including anthocyanins, xanthones, phenolic acids, flavonoids, and flavonols [1,3]. These phytochemicals could exhibit numerous pharmacological activities related to the maintenance of healthy hair and scalp, namely antioxidant, anti-inflammatory, and antimicrobial activities [1,4].…”
Section: Introductionmentioning
confidence: 99%